Effects of rocuronium bromide on globe position and respiratory function in isoflurane‐anesthetized dogs: a comparison between three different dosages. (17th October 2013) - Briganti, Angela; Barsotti, Giovanni; Portela, Diego A.; Di Nieri, Camilla; Breghi, Gloria
Abstract Objective To evaluate the effect on globe position and respiration of three dosages of intravenous rocuronium in isoflurane‐anesthetized dogs. Animal studied Thirty‐two dogs anesthetized for ophthalmic procedures. Procedures The dogs were divided into four groups, each of eight animals (G1‐G4). G1, G2, G3 received 0.075, 0.05, 0.03 mg/kg of IV rocuronium, respectively; G4 received 0.9% NaCl IV; all the treatments were administered when an end‐tidal isoflurane of 1.1–1.2% was reached. Anesthesia was obtained with dexmedetomidine (2.5 mcg/kg IV), methadone (0.1 mg/kg IV), propofol (2 mg/kg IV), and isoflurane in oxygen. Neuromuscular function was assessed with acceleromyography by stimulation of the peroneal nerve using the train‐of‐four (ToF) and the ToF ratio (ToFR). Monitoring of cardiovascular and respiratory functions was performed. Changes in globe position were recorded. Results All three dosages of rocuronium produced centralization of the globe. Duration was 24.3 ± 4.2, 23.4 ± 3.6, and 8.7 ± 2.8 min, for G1, G2, and G3, respectively. The control group did not show globe centralization. No significant differences were found among the four groups in cardiovascular and respiratory parameters. Minute volume and ToFR were significantly lower in G1 compared with baseline values. Conclusions All doses of rocuronium resulted in globe centralization. The higher dose provoked a transient respiratory depression and some degree of skeletal muscular blockade detectable with ToFR. No alterations in respiratory activity were present when 0.05 mg/kg was used. The 0.03 mg/kg dosage could be useful for very short ophthalmic procedures.